ENTEROHEMORRHAGIC Escherichia coli AND ANTIMICROBIAL RESISTANCE OF SWINES BRED IN THE STATE OF PARÁ - Monger, Suellen da Gama Barbosa; Rocha, Daniela Cristiane da Cruz; Costa, Débora de Castro; Souza, Natália Freitas de [UNESP]; Marinho, Anderson Nonato do Rosario; Pereira, Washington Luiz Assunção (Universidade Federal do Paraná, 2022)
The aim of this study was to investigate an occurrence and antimicrobial resistance profile of enterohemorrhagic Escherichia coli in swine bred in Pará State. 200 swine fecal swine samples were collected and seeded in Escherichia coli and Gram negative broths, incubated and then on MacConkey Agar. Suspected colonies were identified on triple sugar iron agar for biochemical characterization and analysed from PCR Multiplex, followed by investigation of susceptibility to available antimicrobial agents using the system VITEK 2 Compact (bioMérieux)™. Of the 15 properties studied, six of them were verified by enterohemorrhagic E. coli (EHEC), being isolated in 11% (22/200) of the researched animals. The antimicrobial susceptibility test showed that 50% of the cases presented resistance to at least one antimicrobial: 31.81% for Nalidixic acid, 27.27% for trimethoprim-sulfamethoxazole, 18.18% for ampicillin and 13.63% for cephalothin. In this study, strains of enterohemorrhagic Escherichia coli were identified in swines and was possible to verify the resistance of these pathogenic strains to some antimicrobials used in veterinary and human routine, such as trimethoprimsulfamethoxazole and ampicillin, which are indicated to combat them, emerging concern regarding the treatment of diseases involving pathogenic E. coli, as well as the selection of resistance genes in bacteria present in the animal microbiota used as a food, and the possibility of transferring these genes to bacteria of the human intestinal tract.
(Escherichia coli enterohemorrágica e perfil de resistência a antimicrobianos em suínos criados no estado do Pará)
Keywords: Diarrhea; Enteropathogens; Swine farming